Identification of 2-(N-aryl-1,2,3-triazol-4-yl) quinoline derivatives as antitubercular agents endowed with InhA inhibitory activity - Sabt, Ahmed; Abdulla, Maha-Hamadien; Ebaid, Manal S.; Pawełczyk, Jakub; Abd El Salam, Hayam A.; Son, Ninh The; Ha, Nguyen Xuan; Vaali Mohammed, Mansoor-Ali; Traiki, Thamer; Elsawi, Ahmed E.; Dziadek, Bozena; Dziadek, Jaroslaw; et al. (Frontiers in Chemistry, 2024)
The spread of drug-resistant tuberculosis strains has become a significant economic burden globally. To tackle this challenge, there is a need to develop new drugs that target specific mycobacterial enzymes. Among these enzymes, InhA, which is crucial for the survival of Mycobacterium tuberculosis, is a key target for drug development. Herein, 24 compounds were synthesized by merging 4-carboxyquinoline with triazole motifs. These molecules were then tested for their effectiveness against different strains of tuberculosis, including M. bovis BCG, M. tuberculosis, and M. abscessus. Additionally, their ability to inhibit the InhA enzyme was also evaluated. Several molecules showed potential as inhibitors of M. tuberculosis. Compound 5n displayed the highest efficacy with a MIC value of 12.5 μg/mL. Compounds 5g, 5i, and 5n exhibited inhibitory effects on InhA. Notably, 5n showed significant activity compared to the reference drug Isoniazid. Molecular docking analysis revealed interactions between these molecules and their target enzyme. Additionally, the molecular dynamic simulations confirmed the stability of the complexes formed by quinoline-triazole conjugate 5n with the InhA. Finally, 5n underwent in silico analysis to predict its ADME characteristics. These findings provide promising insights for developing novel small compounds that are safe and effective for the global fight against tuberculosis.